A rare case of sacrococcygeal squamous cell carcinoma - Elsonmond Vick, Duin; Ravin, Prabaharan; Mohammad Zaki, Haji Mohd Amin; Chan, Wai Hoong (2021)
Introduction: Sacrococcygeal neoplastic lesions are extremely rare. Primary benign or malignant lesion are lesser than 7% of all intraspinal lesions. Patients with sacral tumors present with non-specific symptoms, including pain, palpable mass, and neurologic deficits. Despite the advancement of imaging modalities, it is still a diagnostic and therapeutic challenge. Squamous cell carcinoma (SCC) of this area is very rare. A few case reported with acquired condition or underlying congenital or developmental remnants. A chronic sacrococcygeal pilonidal disease with SCC transformation is described by Michalopoulos et al. Demirel AH et al reported the incident of SCC with underlying tailgut cyst in 73 yearold female. CT-scan and MRI is done to define the anatomic origin, extent, and radiologic features of a given lesion. Biopsy is commonly performed to obtain histologic diagnosis. In this paper we report a primary squamous cell carcinoma in this region. Discussion: A 52 year-old lady who presented with five months history of painless right-sided sacral swelling associated with right radicular pain, urinary incontinence and constipation. No constitutional symptoms. The swelling is 8x8 cm in size, firm to hard consistency, non-mobile, smooth surface, illdefined border and not fixed to the overlying skin. Plain X-Ray of Pelvis revealed right sided sacrococcygeal expensile lytic lesion with ill-defined margin. CT-Scan of pelvis showed sacrococcygeal heterogenous mass associated with bony destruction and compression on bladder and rectum. MRI revealed aggressive sacrococcygeal mass with local bony invasion and sacral nerve root S2-S5 involvement. Biopsy was performed and HPE result was consistent with Squamous Cell Carcinoma (SCC). Systemic staging showed metastases to bilateral lungs. Palliative Care was planned with multidisciplinary team involvement. Conclusion: Sacrococcygeal Squamous Cell Carcinoma is very rare. Diagnosis remained challenging even with advancement of imaging modalities. Biopsy is required to confirm tissue diagnosis. Treatment requires multi-disciplinary team approach to ensure survival of the patient